Dampak Perkembangan Pariwisata Pantai Tambakrejo Terhadap Ekonomi Masyarakat Desa Tambakrejo Kabupaten Blitar - Nugraheni, Gendis Wedar; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p07, 2018)
Tambakrejo Beach is located in Tambakrejo Village, Wonotirto district, South of Blitar City. Communities around the Tambakrejo Beach initially work as fishermen, traders, farmers, and to meet the daily needs in getting from fishing. However today many people are turning their professions into traders. The tourism development of Tambakrejo beach resulted in changes of community activities. The method used to collect the data in this study are observation, interview, questionnaires, and literature study and the methods used to analyze the data is comparative descriptive analysis method. The results of this study related to the tourism development that tourists visits increases every year. The interaction of tourists with the community is also high, the number of tourist facilities increased, the attractions are two activities such as boating and riding ATV and watching Islamic local culture Larung Sesaji in the beach, and promotion is done with social media and cooperation between magazine and television to review Tambakrejo in their program . The results of the tourism development toward communities economy is community income increased and employment opportunities associated with the movement of livelihoods as a trader.   Keywords : The Impact, Tourism Development, Community Economy, Tambakrejo